Preliminary Study on Marine Ecological Environment Problems and Prevention Points in Fujian Province (Journal of Environmental Science Studies, 2022)
With the gradual promotion and implementation of the strategy of Fujian Province as a strong marine economy, the marine economy of Fujian Province has been effectively developed. However, due to various historical reasons, long-term indiscriminate exploitation of marine resources, dredging, damming and predatory development of marine tourism have led to the destruction of marine ecosystems and seriously restricted the sustainable development of marine economy. Based on the reading and research of numerous relevant literature, this paper integrates and expounds the current situation and background of marine pollution investigation in Fujian Province, analyzes and puts forward the corresponding prevention and control measures and key points.